Climate Change, Carbon Tax, and the Indonesian Directorate General of Taxes Preparedness in Implementing the New Carbon Tax - Ryan Nugraha; Paul Balogun (Yayasan Ilomata, 2022)
One of the crucial issues in Indonesia is climate change. It can jeopardize Indonesia's sustainable development. This article investigates a carbon tax as a climate policy option in Indonesia and the Directorate General of Taxes readiness in imposing the new carbon tax bill in April 2022. This research analyzes the early stage of carbon tax implementation in Indonesia. The author conducted a qualitative questionnaire to a small and unrepresentative sample of 32 tax officers in the DGT's head office, regional office, and small tax office in Jakarta. The data collecting process took place in January 2022. The results suggest that most DGT's employees in this study are already familiar with the term